Sequential evolution of antidote and toxin links genetic incompatibility with immune responses - Dongying Xie; Yiming Ma; Junhui Zeng; Pohao Ye; Zhongying Zhao (Proceedings of the National Academy of Sciences, 2026)
Toxin-antidote (TA) systems are selfish genetic elements that ensure their own inheritance by eliminating offspring that do not inherit the module, thereby creating postzygotic genetic incompatibilities both within and between species. Despite their ubiquity and substantial fitness costs, the origin and persistence of TA systems remain poorly understood. Here, we report a TA gene pair in the nematode Caenorhabditis nigoni . The antidote gene, Cni-shls-2 , is a C. nigoni -specific F-box gene that arose through recent tandem duplications, leading to three identical copies. Its absence results in embryonic lethality in both C. nigoni and its hybrids with the sister species Caenorhabditis briggsae . This lethality is mediated by a maternally deposited toxin, Cni-hlix-1 , a chimeric gene formed by the fusion of duplicated host sequences with novel sequences that could be derived from bacteria/archaea. Analysis of evolutionary trajectory of the TA genes among various populations suggests that the antidote is more likely to predate the toxin. These results support a possible model of TA origin, in which Cni-shls-2 initially evolved under pathogen pressure, whereas the subsequent emergence of the toxin enforces antidote retention. We speculate that host–pathogen conflict may serve as a key driving force in the evolution and maintenance of TA systems, inadvertently leading to reproductive barriers.